Asymmetric coupling in multi-channel simple exclusion processes - Cai, Z-P; Yuan, Y-M; Jiang, R; Hu, Mao Bin; Wu, Q-S; Wu, Yong Hong (IOP Publishing, 2008)
In this paper, we investigate N-channel simple exclusion processes in which particles can move across N parallel lattices and jump fully asymmetrically between the channels. Monte Carlo simulations are carried out to investigate the phase diagrams and density profiles of the system. It is shown that the phase diagram structure changes with increase of N. Moreover, how the phase diagram depends on N is obtained. A vertical cluster mean-field analysis is carried out; it shows good agreement with simulations.